In situ nuclear matrix preparation in Drosophila melanogaster embryos/tissues and its use in studying the components of nuclear architecture. Issue 1 (31st December 2022) - Pathak, Rashmi U; Bihani, Ashish; Sureka, Rahul; Varma, Parul; Mishra, Rakesh K
ABSTRACT: The study of nuclear matrix (NuMat) over the last 40 years has been limited to either isolated nuclei from tissues or cells grown in culture. Here, we provide a protocol for NuMat preparation in intact Drosophila melanogaster embryos and its use in dissecting the components of nuclear architecture. The protocol does not require isolation of nuclei and therefore maintains the three-dimensional milieu of an intact embryo, which is biologically more relevant compared to cells in culture. One of the advantages of this protocol is that only a small number of embryos are required. The protocol has been extended to larval tissues like salivary glands with little modification. Taken together, it becomes possible to carry out such studies in parallel to genetic experiments using mutant/transgenic flies. This protocol, therefore, opens the powerful field of fly genetics to cell biology in the study of nuclear architecture. Summary : Nuclear Matrix is a biochemically defined entity and a basic component of the nuclear architecture. Here we present a protocol to isolate and visualize Nuclear Matrix in situ in the Drosophila melanogaster and its potential applications.